PENGGUNAAN DIGITAL ADVERTISING DALAM PROMOSI CHAMPIONSHIP EVENT OLEH MYEDUSOLVE - Dara Syafira; Djuni Akbar (Bisnis Event, 2023)
Digitalization in the use of information and communication technology is growing in all countries including Indonesia, through programs launched by Kominfo. To keep abreast of developments in technology and information, human resources are needed. So, an EduTech Startup emerged which has the goal of empowering the workforce in Indonesia through digital learning, certification and skills upgrading programs so they are ready for a career. MyEduSolve startup where the writer carried out the Field Work Practice for 6 months. Advertising through social media such as Instagram, Twitter, Facebook and Youtube has a big impact. It can reach a wider target quickly. It can be utilized in the promotion process so that it is right on target. MyEduSolve promotion strategy in the Microsoft Office Specialist & Adobe Certified Professional National Championship Event 2021 focuses on the use of technology. This study aims to present the event planning process, strategies for promoting events, as well as the implementation of digital advertising implemented by MyEduSolve. The method used in this research is through interviews, observation, and documentation. Obtained in planning an event has 4 stages, namely the preparation of the event framework, the stage of analyzing target participants, the stage of determining the event timeline, and the stage of publishing the event with promotion using advertising. MyEdusolve uses a promotional strategy by placing digital advertisements and direct marketing by implementing advertising objectives, namely informing, persuading, and adding value so that the message to be conveyed is eyed by the target audience.